Geomorphology of craters located at Mercury’s north pole - Silvia Bertoli; Alice Lucchetti; Maurizio Pajola; Elena Martellato; Matteo Massironi; Pamela Cambianica; Emanuele Simioni; Gabriele Cremonese (Journal of Maps)
We present the first highly detailed morphological analysis of three craters located in Mercury's north pole, characterized by permanently shadowed regions (PSRs). This study, which began with an initial sample of 14 craters, highlighted three morphological classes, based on the craters’ features: Complete complex morphology, Flat-floor morphology, and Immature complex morphology, presented here as maps of three representative craters, one for each class. As demonstrated by decades of studies, areas of PSRs within these craters could host water ice deposits, making them among the most interesting targets for future studies by the ESA/JAXA’s BepiColombo mission. Our mapping work aims to give a cartographic context to subsequent chronological, thermal, and compositional analyses, as well as to provide a support to the acquisition strategy of the BepiColombo mission upon its arrival on Mercury in late 2025. The mapping highlights landforms which might be related to volcanic, gravitational, and maybe periglacial events.